A Critical Overview on the Effect of Microwave Irradiation in Organic Synthesis. Issue 1 (23rd July 2018) - Díaz‐Ortiz, Á.; Prieto, P.; de la Hoz, A.
Abstract: Despite the great success of Microwave Assisted Organic Synthesis (MAOS) there is still a lack of knowledge about the interaction of the electromagnetic radiation with matter. In consequence, it has been very difficult to rationalize the effect of microwave irradiation in chemistry, to determine the existence of microwave effects (thermal and non‐thermal) and to develop predictive models on the characteristics required for a reaction to be improved under microwaves. This has been a handicap to develop new chemistry under microwave irradiation and the origin of many controversies. This personal account collects some new findings in this field and our work on the use of computational chemistry to develop predictive models and to determine parameters related to thermal and non‐thermal effects, with clear advantages over experimental methods where separation of these effect is almost impossible. Abstract : Computational Methods are used to elucidate Microwave effects and to design predictive models in MAOS.